The Effect of Nebulized Magnesium Sulphate on the Incidence of Postoperative Sorethroat - T. Padma; Raju B; Raviraj GS (Academia Anesthesiologica International, 2020)
Background: Postoperative sore throat (POST) is a well-recognized complication that remains unresolved in patients undergoing endotracheal intubation for general anaesthesia. The wide variation in these figures is presumably due to different skills and techniques among anesthetists and to differences between patients in the definition of sore throat. The main aim is to study the attenuating effect of Magnesium sulphate nebulization on the incidence of post-operative sore throat. Subjects and Methods: This is a prospective randomized clinical study. A total number of 100 patients of ASA grade 1 & 2, in the age group of 18 - 60 years. The study has been carried out at Sri Venkateswara Ram Narayana Ruia Government General Hospital, Sri Venkateswara Medical College, Tirupati, over a period of 12 months. Results: There was no significant difference among the groups in terms of age, gender and weight. Whereas Magnesium sulphate significantly lessens the POST during swallowing at 4th hour as compared to Normal saline (p< 0.05) and this statement can be attributed to any population. Conclusion: Post-operative sore throat is one of the most common undesirable anesthesia-associated problems in the patients undergoing GA with an endotracheal tube for routine surgical cases for up to 24 h. Magnesium sulphate was significantly reduces the incidence of POST compared to Normal saline , and it is safe, simple and effective in reducing postoperative sore throat.